Assessing the value of diagnostic tests: a framework for designing and evaluating trials. (21st February 2012) - Ferrante di Ruffano, Lavinia; Hyde, Christopher J; McCaffery, Kirsten J; Bossuyt, Patrick M M; Deeks, Jonathan J
Abstract : The value of a diagnostic test is not simply measured by its accuracy, but depends on how it affects patient health. This article presents a framework for the design and interpretation of studies that evaluate the health consequences of new diagnostic tests